Conflict Resolution, Prevention and Handling Public Information Disputes - Agustina, Dini; Jamalullail, Jamalullail; Subhan, Arief (Jurnal Indonesia Sosial Sains, 2024)
Conflicts over public information disputes have increased in the past three years. This study aims to analyze the process of information flow that occurs in information dispute conflicts and to analyze solutions to prevent and handle information dispute conflict problems. This study intends to analyze conflict resolution resolution of public information disputes in Indonesia using communication theory and conflict resolution theory in depth. The methodology in this research is qualitative method using library research method. Based on the results of the research analysis, it was concluded that the process of information flow that occurs in conflicts over public information disputes is hampered due to dissatisfaction from public information applicants with requests for information submitted from public bodies, because there are differences in perception. The solution to conflict prevention is increased awareness of the parties involved regarding rights and obligations related to public information, training and education on public information disclosure, formulation of clear policies on related Standard Operating Procedures and increased internal mediation between public bodies and information applicants. In addition, solutions for handling information dispute conflicts, in addition to mediation and adjudication in accordance with regulations, can be improved through increasing understanding of regulations regarding Public Information Disclosure and increasing the institutional capacity of the Information Commission.